Angiopoietin-2 mediates thrombin-induced monocyte adhesion and endothelial permeability - Rathnakumar, Kumaragurubaran; Augustin, Hellmut (Journal of thrombosis and haemostasis, 2016)
Essentials Mechanism of thrombin-induced inflammation is not fully understood. Thrombin induced monocyte adhesion and barrier loss require Angiopoietin-2 (Ang-2). Ang-2 mediates vessel leakage and monocyte adhesion through SHP-2/p38MAPK pathway. Calcium dependent SHP2/p38MAPK activation regulates Ang-2 expression through a feedback loop. Summary Background Thrombin imparts an inflammatory phenotype to the endothelium by promoting increased monocyte adhesion and vascular permeability. However, the molecular players that govern these events are incompletely understood. Objective The aim of this study was to determine whether Angiopoietin-2 (Ang-2) has a role, if any, in regulating inflammatory signals initiated by thrombin. Methods Assessment of vascular leakage by Miles assay was performed by intra-dermal injection on the foot paw. Surface levels of intercellular adhesion molecule-1 (ICAM-1) were determined by flow cytometry. Overexpression, knockdown and phosphorylation of proteins were determined by Western blotting. Results In time-course experiments, thrombin-stimulated Ang-2 up-regulation, peaked prior to the expression of adhesion molecule ICAM-1 in human umbilical vein-derived endothelial cells (HUVECs). Knockdown of Ang-2 blocked both thrombin-induced monocyte adhesion and ICAM-1 expression. In addition, Ang-2−/− mice displayed defective vascular leakage when treated with thrombin. Introducing Ang-2 protein in Ang-2−/− mice failed to recover a wild-type phenotype. Mechanistically, Ang-2 appears to regulate the thrombin-activated calcium spike that is required for tyrosine phosphatase SHP2 and p38 MAPK activation. Further, down-regulation of SHP2 attenuated both thrombin-induced Ang-2 expression and monocyte adhesion. Down-regulation of the adaptor protein Gab1, a co-activator of SHP2, as well as overexpression of the Gab1 mutant incapable of interacting with SHP2 (YFGab1), inhibited thrombin-mediated effects, including downstream activation of p38 MAPK, which in turn was required for Ang-2 expression. Conclusions The data establish an essential role of the Gab1/SHP2/p38MAPK signaling pathway and Ang-2 in regulating thrombin-induced monocyte adhesion and vascular leakage.